Measuring The First-Year Students’ Ability of English Study Program on English Grammar in Academic Year 2023/2024 - Lumban Raja, Viator; Pangaribuan, Jontra Jusat; Naibaho, Lisna (English Lecturers and Teachers Association (ELTA), 2025)
This study investigated the grammar proficiency of first-year students enrolled in the English Study Program during the 2023/2024 academic year. A quantitative descriptive approach with a post-test-only design was employed, involving 22 participants. Data were collected through a standardized 30-item multiple-choice test that assessed 17 key grammar topics, including tenses, passive voice, conditionals, and relative pronouns. The results indicated that students achieved a mean score of 45.14, categorized as